Farmer perspectives about cover crops by non-adopters - Myers, Robert L.; Wilson, Kelly R. (Frontiers in Sustainable Food Systems, 2023)
The SARE/CTIC national farmer survey has assessed farmer experiences and perceptions about cover crops six times from early 2013 to early 2020. In most years, approximately 2,000 farmers responded to the survey questions, a majority of which were cover crop adopters, but a significant fraction (7% to 16%) were non-adopters: farmers not yet using cover crops. Survey reports previously focused on the experiences of cover crop adopters. In this paper, we synthesize responses of non-adopters to examine what factors influence or constrain adoption of cover crops. The non-adopters had similar farm sizes and land tenure situations compared to cover crop adopters, but were more likely to make use of conventional tillage and less likely to use continuous no-till compared to cover crop adopters. Non-adopters identified a number of concerns about cover crops, with the top concern being the time to plant and manage cover crops. Approximately 80% of non-adopters reported being open to considering cover crops. Factors cited to encourage non-adopters to adopt cover crops included incentive payments, tax breaks, crop insurance discounts, and soil carbon payments. Non-adopters wanted to gain a better understanding of how cover crops would benefit their particular farming operation and were interested to gain training through local cover crop workshops, local cover crop field demonstrations and one-on-one technical assistance. Non-adopters were particularly interested in how cover crops could boost soil organic matter and also wanted to know how cover crops could help with yields and reducing input costs.